2003
DOI: 10.1210/en.2002-220968
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hepatic GLUT8 Expression in Normal and Diabetic Models

Abstract: GLUT8 is a novel glucose transporter protein that is widely distributed in tissues including liver, a central organ of regulation of glucose homeostasis. The purpose of the current study was to investigate expression and regulation of hepatic GLUT8 mRNA and protein. Therefore, Northern and immunoblot analysis, semiquantitative RT-PCR, and immunofluorescence microscopy were performed using mouse livers at different stages of embryonic and postnatal development and in type 1 (streprozotocin treated) and type 2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 32 publications
(54 reference statements)
3
40
0
Order By: Relevance
“…This suggests that both GLUT 8 and GLUT4 expression in WAT is insulin sensitive. This is consistent with the earlier study in rat in which hyperinsulinemia was found to be associated with an increased level of GLUT8 protein in adipocytes (Gorovits et al, 2003). Our study demonstrates that GLUT4 and GLUT8 expression is differentially regulated in adipose tissue in response to insulin and suggests that GLUT8 and GLUT4 concentrations in adipose tissue are intimately linked to glucose homeostasis.…”
Section: Effect Of Insulin On Expression Of Phosphorylated Mapks In Wsupporting
confidence: 93%
“…This suggests that both GLUT 8 and GLUT4 expression in WAT is insulin sensitive. This is consistent with the earlier study in rat in which hyperinsulinemia was found to be associated with an increased level of GLUT8 protein in adipocytes (Gorovits et al, 2003). Our study demonstrates that GLUT4 and GLUT8 expression is differentially regulated in adipose tissue in response to insulin and suggests that GLUT8 and GLUT4 concentrations in adipose tissue are intimately linked to glucose homeostasis.…”
Section: Effect Of Insulin On Expression Of Phosphorylated Mapks In Wsupporting
confidence: 93%
“…GLUT8 gene expression decreased following glucose deprivation or hypoxia in cultured, differentiated 3T3-L1 adipocytes; however, the conditions tested were beyond the physiologic range [137]. GLUT8 expression in liver is restricted to a single layer of hepatocytes surrounding central veins similar to GLUT1 [141]. The highly glycolytic nature of pericentral hepatocytes suggests GLUT8 involvement in substrate shuttling through the glycolytic pathway [141].…”
Section: Glut8mentioning
confidence: 99%
“…GLUT8 expression in liver is restricted to a single layer of hepatocytes surrounding central veins similar to GLUT1 [141]. The highly glycolytic nature of pericentral hepatocytes suggests GLUT8 involvement in substrate shuttling through the glycolytic pathway [141]. The zonation of GLUT8 expression is altered in type 1 and type 2 diabetic mice models further pointing to GLUT8 involvement in hepatocyte adaptation to altered glucose homeostasis [141].…”
Section: Glut8mentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that surface SLC2A8 expression is regulated by the insulin/ insulin-like growth factor-1 (IGF1) signaling pathways through the IGF1 receptor in the mouse blastocyst (Carayannopoulos et al 2000, Pinto et al 2002. In different diabetic models, hepatic SLC2A8 has shown altered expression patterns (Gorovits et al 2003). We have also reported that SLC2A9 protein expression was significantly increased in the kidney and liver from STZinduced diabetic mice compared with non-diabetic mice (Keembiyehetty et al 2006).…”
Section: Introductionmentioning
confidence: 99%